1990
DOI: 10.2151/jmsj1965.68.3_335
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Measurements of Optical Properties of Tropospheric Aerosols over an Urban Area

Abstract: Aircraft measurements of aerosol sizes, intensities of direct-solar and circumsolar (aureole) radiations, and upward and downward fluxes of solar radiation were carried out over Nagoya, a typical urban area in Japan, using an optical particle counter, an aureolemeter and spectral pyranometers, respectively. Vertical profiles of optical thicknesses and volume spectra of aerosols have been successfully retrieved by inverting measured aureole intensities. The obtained values have been utilized to estimate the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 32 publications
4
4
0
Order By: Relevance
“…We measured these bimodal distributions over the height range of the measurement between 0.6 and 5.5 km. The bimodal size distributions have frequently been observed in the troposphere over around Japan [Tanaka et al, 1990;Hayasaka et al, 1998]. Our results of the chemical analyses showed that the bimodal shapes were composed primarily of sulfates in the fine mode and mineral dusts and/or sea salts in the coarse mode.…”
Section: Particle Size Distribution and Number Concentrationsupporting
confidence: 59%
“…We measured these bimodal distributions over the height range of the measurement between 0.6 and 5.5 km. The bimodal size distributions have frequently been observed in the troposphere over around Japan [Tanaka et al, 1990;Hayasaka et al, 1998]. Our results of the chemical analyses showed that the bimodal shapes were composed primarily of sulfates in the fine mode and mineral dusts and/or sea salts in the coarse mode.…”
Section: Particle Size Distribution and Number Concentrationsupporting
confidence: 59%
“…The most signi® cant discrepancies appear in the function minimum, which decreases when the value assigned to the imaginary part of m increases. These results are similar to those obtained by Tanaka et al (1990 ) who found that uncertainties in the retrieved t a l due to the uncertainty in the ® xed refractive index are lower than 10%.…”
Section: Inversion Resultssupporting
confidence: 91%
“…The contribution of the background stratospheric aerosol amount to the total amount is so small that almost all of the columnar aerosols consist of tropospheric aerosols for the periods except the El Chichon event. For example, Ta (500) of stratospheric aerosols for the non-El Chichon periods is about 0.02 or less (Nakajima et al, 1986a;Tanaka et al, 1990) so that the contribution of the background stratospheric aerosols to the columnar total aerosols is expected to be small.…”
Section: B the El Chichon Aerosolsmentioning
confidence: 99%
“…The accumulation mode aerosols are usually found in the planetary boundary layer, while coarse-particle mode aerosols are found in and above the planetary boundary layer. Cress, 1981, 1983;Tanaka et al, 1990;Hayasaka et al, 1990). It is, therefore, reasonable to infer that the accumulation mode aerosols of summer are substances of surface origin, and grow by condensation and coagulation under high temperature and abundant water vapor conditions.…”
Section: B the El Chichon Aerosolsmentioning
confidence: 99%